Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1002/crat.2170300417
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Spectroscopy of Defect States in Etched and Air‐annealed CuInSe2 Single Crystals

Abstract: Photoacoustic spectra of cleaved, polished and etched, and air-annealed n-type CuInSe, single crystals are measured at different frequencies between 30 and 312 Hz. The spectra related to the bulk of the crystals exhibit five structures due to defects that are also present in p-type crystals. Polishing and etching as well as subsequent air annealing at 100, 200 and 300 "C reveal rather complex changes of the defect equilibrium in the near-surface region of the crystals which include both relative concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…It has also been suggested that the acceptor concentration remains practically unchanged during this process (CAHEN, NOUFI; NOUFI, CAHEN). However, recent electron paramagnetic resonance (PADAM et al) and photoacoustic spectroscopy (ZEGADI et al 1995) studies in this compound indicate that oxygen affects not only the donor but also the acceptor concentrations. In addition, it has also been found (HABA et al) that the incorporation of In 2 O 3 in CuInSe 2 thin films leads to an increase in the ratio of copper to indium atoms.…”
Section: Introductionmentioning
confidence: 94%
“…It has also been suggested that the acceptor concentration remains practically unchanged during this process (CAHEN, NOUFI; NOUFI, CAHEN). However, recent electron paramagnetic resonance (PADAM et al) and photoacoustic spectroscopy (ZEGADI et al 1995) studies in this compound indicate that oxygen affects not only the donor but also the acceptor concentrations. In addition, it has also been found (HABA et al) that the incorporation of In 2 O 3 in CuInSe 2 thin films leads to an increase in the ratio of copper to indium atoms.…”
Section: Introductionmentioning
confidence: 94%